An account of practice: employing drawings and stories to enable reflective learning. (2nd January 2019) - Robertson, Jane; le Sueur, Heidi; Terblanche, Nicky
ABSTRACT: Facilitating reflection for personal growth in a business context requires careful thought and planning. As a learning process, Business-Driven Action Learning (BDAL) has two points of focus. It aims to firstly identify and make recommendations regarding a business challenge, whist secondly facilitating potentially significant individual personal learning and growth. The research reported in this account of practice focused on personal learning by exploring the potential for individuals to experience transformative learning during a BDAL process. During the research I used a number of methods including hand-drawn images and in-depth interviews to enable the writing of interpretive stories. Findings revealed that participants found reflection during and after the BDAL beneficial. They gained insights into what they learnt, what changed since the BDAL experience and also what they still need to focus on. The findings have practical implications for the action learning facilitator of BDAL during management development programmes. One of the ways action learning facilitators can initiate the reflection process of new participants is to share the experience of previous participants. 'Sandy's interpretive story', contained in this article, is such an example and includes hand-drawn images of her learning journey. I argue that the use of interpretative stories helps new participants understand programme challenges and stimulates their individual learning journey.